The Australian Treatment Outcomes Profile instrument as a clinical tool for older alcohol and other drug clients: A validation study. (13th April 2016) - Lintzeris, Nicholas; Monds, Lauren A.; Rivas, Gonzalo; Leung, Stefanie; Withall, Adrienne; Draper, Brian
Abstract: Introduction and Aims: The Australian Treatment Outcomes Profile (ATOP) is a brief instrument that assesses a range of substance use, health and well‐being measures over the past 28 days. Previously, it has been validated in general adult Australian alcohol and other drug (AOD) treatment populations. However, the increasing number of older‐aged clients attending AOD treatment warrants the instrument to be validated for this population. The aim of this study was to validate the ATOP for use in older AOD populations, by comparing it with validated 'gold standard' measures used in older populations. Design and Methods: A convenience sample of 99 participants aged ≥50 attending specialist AOD services in Sydney, Australia were administered the ATOP by a researcher, along with alcohol use (AUDIT) and health questionnaires [Physical Health Questionnaire‐15, 12‐item short‐form Health Survey (SF‐12) and Geriatric Depression Scale]. Results: The ATOP items had strong agreement with the comparison instruments. The highest correlation was between the 28 days alcohol use and the AUDIT. ATOP psychological health scores highly correlated with the SF‐12 mental health subscale and the Geriatric Depression Scale, and ATOP physical health scores significantly correlated with the SF‐12 physical health subscale and the Physical Health Questionnaire‐15. The ATOP Quality of Life score significantly correlated with all health measures. Discussion and Conclusions The ATOP has good concurrent validity with other validated substance use and health measures in an older population. Comparison with general older populations demonstrated the poorer health of this group of older AOD clients in particular.[Lintzeris N, Monds L A, Rivas G, Leung S, Withall A, Draper B. The Australian Treatment Outcomes Profile instrument as a clinical tool for older alcohol and other drug clients: A validation study. Drug Alcohol Rev 2016;35:673‐677]